2022
DOI: 10.1038/s41598-022-08451-2
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium adsorption performance and mechanism from aqueous solution using red mud modified with amorphous MnO2

Abstract: In this study, red mud modified by manganese dioxide(MRM) was utilized as an adsorbent to effectively remove Cd2+ from aqueous solution. The characteristics were analysed by SEM–EDS, XRD, BET, FTIR and XPS. Different factors that affected the Cd2+ removal on MRM, such as dosage, initial pH, initial Cd2+ concentration, were investigated using batch adsorption experiments. Simultaneously, the adsorption kinetics, adsorption isotherms and adsorption thermodynamics of Cd2+ were also investigated using adsorption e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 51 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…The functional groups in IMC were also detected by FTIR, as shown in Fig. 2 f. The wavenumber of 3432, 1632, and 1446 cm −1 was related to the vibration of –OH, C=O, and C–C, respectively 36 , 37 . These results demonstrated that the abundant functional groups on the IMC800 materials with various red mud loading rates.…”
Section: Resultsmentioning
confidence: 96%
“…The functional groups in IMC were also detected by FTIR, as shown in Fig. 2 f. The wavenumber of 3432, 1632, and 1446 cm −1 was related to the vibration of –OH, C=O, and C–C, respectively 36 , 37 . These results demonstrated that the abundant functional groups on the IMC800 materials with various red mud loading rates.…”
Section: Resultsmentioning
confidence: 96%
“…31 b. Thus, the significant attenuation of the O–H peak at 3740 cm −1 can be attributed to the fact that this functional group is involved in the adsorption process 23 , 68 .…”
Section: Resultsmentioning
confidence: 97%
“…In the intraparticle diffusion process (second region) there is a gradual decrease in adsorption at the sites on the adsorbent surface (adsorption capacity reaches the maximum value). Then, cadmium adsorption takes place on the available sites inside the adsorbent, generating significant mass transfer resistance and reaching the adsorption equilibrium and the adsorption rate gradually decreases 68 70 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the pseudo-second-order model assumes that sorption site occupation is proportional to the square of the number of empty sites. The pseudo-second-order equation is written in the linear form as (Pang et al 2022):…”
Section: Kinetics Of Adsorptionmentioning
confidence: 99%